Biocatalytic Synthesis and Polymerization via ROMP of New Biobased Phenolic Monomers: A Greener Process toward Sustainable Antioxidant Polymers - Diot-Néant, Florian; Migeot, Loïs; Hollande, Louis; Reano, Felix A.; Domenek, Sandra; Allais, Florent (Frontiers in Chemistry, 2017)
Antioxidant norbornene-based monomers bearing biobased sterically hindered phenols (SHP) - NDF (norbornene dihydroferulate) and NDS (norbornene dihydrosinapate) - have been successfully prepared through biocatalysis from naturally occurring ferulic and sinapic acids, respectively, in presence of Candida antarctica Lipase B (Cal-B). The ring opening metathesis polymerization (ROMP) of these monomers was investigated according to ruthenium catalyst type (GI) vs. (HGII) and monomer to catalyst molar ratio ([M]/[C]). The co-polymerization of antioxidant functionalized monomer (NDF or NDS) and non-active norbornene (N) has also been performed in order to adjust the number of SHP groups present per weight unit and tune the antioxidant activity of the copolymers. The polydispersity of the resulting copolymers was readily improved by a simple acetone wash to provide antioxidant polymers with well-defined structures. After hydrogenation with p-toluenesulfonylhydrazine (p-TSH), the radical scavenging ability of the resulting saturated polymers was evaluated using α,α-diphenyl-β-picrylhydrazyl (DPPH) analysis. Results demonstrated that polymers bearing sinapic acid SHP exhibited higher antiradical activity than the polymer bearing ferulic acid SHP. In addition it was also shown that only a small SHP content was needed in the copolymers to exhibit a potent antioxidant activity.